Análise econômica, social e ambiental dos resíduos sólidos urbanos produzidos no Município de Barra do Bugres – MT - da Silva, Fabrício Schwanz; Leite, Max George França; de Lazari, Tatiane Aparecida (Revista Gestão da Produção Operações e Sistemas, 2006)
The problem generated by the pollution of the environment, as well as its scarcity, is a theme for major world discussions. That’s why many of them are not renewable and are limited. One efficient resource presented to the solution of the solid urban residues is the accomplishment of the selective collection and afterwards, the recycling of the inorganic materials, which help in the environmental preservation, income generation and social reintegration, among others. This paper had the purpose of evaluating and the quantifying of the amount collected from the urban solid residues in the city of Barra do Bugres, Brazil, co-relating them with the monetary value of the inorganic materials, this way computing financial, social and environmental losses in the city, caused by the absence of the selective collection and recycling. By means of the obtained results, it is concluded that, the municipality fails to collect an amount of R 1,417,852.8 yearly due to the lack. of a rational and efficient waste collection and treatment system. This very process allows for the recycling and its benefíts, such as: environmental preservation, income generation, employment generation, that is, promoting a social, economic and environmental feedback, and this allows for life quality improvement for the population. Keywords: Urban solid residues; Selective collection; Recycling.